Comparison of filter line search algorithms in the primal-dual barrier approach for nonlinear programming - Costa, M. Fernanda P. (2009)
In this paper, we present a new filter line search method based on two measures that is integrated into the primal-dual barrier method developed by Wachter and Biegler [Mathematical Programming 106 (2006), pp. 25--57] for nonlinear programming. One measure arises directly from the first order optimality conditions of the problem and the other is the barrier function. Primary assessment of the method has been done with a well-known collection of problems and compared with the solver IPOPT.